Design of an IoT-Based Earthquake Vibration Detection System Using MPU6050 Sensors with Real-Time Monitoring via a Mobile App - Dwiputra, Audry Zaky; Nazry S, Hevlie Winda (Jurnal ICT : Information and Communication Technologies, 2026)
Advances in Internet of Things (IoT) technology enable electronic devices to communicate and exchange data in real time. This study aims to design and implement an IoT-based earthquake vibration detection system using an MPU6050 sensor and an ESP32 microcontroller with real-time monitoring via a mobile application. The research method used is engineering research with an iterative prototype approach. The system consists of an MPU6050 sensor as a vibration detector, ESP32 as a data processor and communication module, an IoT server, an LCD display, a buzzer, and a mobile application as the user interface. Acceleration data on the X, Y, and Z axes is processed using a threshold-based method to distinguish between normal conditions and earthquake events. The test results show that the system achieves a detection accuracy of 92.6%, with an average response time of 1.2 seconds from vibration detection to mobile notification delivery. In addition, the system demonstrates a data transmission reliability of 98.3%, indicating stable communication between the device and the IoT server. The system is capable of detecting vibration changes effectively, transmitting data in real time, and displaying monitoring information through a mobile application. Early warning notifications are successfully generated when vibration values exceed the defined threshold. Based on the results, the proposed system provides a low-cost, efficient, and easy-to-implement solution for earthquake vibration monitoring on a local scale. However, improvements are still required in adaptive threshold optimization and large-scale field testing to enhance system robustness and reliability under real-world conditions.